Determination of the Rational Mode of Mutual Loading of Traction Engines of Main Electric Locomotives - Arpul, S. V; Afanasov, A. M; Bilukhin, D. S; Vasyliev, V. Y; Shapovalov, O. S; Buriak, S. Y (Science and Transport Progress, 2022)
Purpose. The actual state of many of the existing testing stations for traction electric machines does not meet modern requirements for the organization of repair and technical control. At most of these stations, mutual loading stands with low energy efficiency are used. The purpose of the work is to determine the rational mode of loading electric traction machines, which will ensure a decrease in the total power of the power sources of the test station, an increase in energy efficiency and the quality of tests. Methodology. The methodological basis of the work is the general theoretical provisions and principles of the systematic approach of theoretical electrical engineering, theoretical mechanics, the theory of electric machines and converters. The substantiation of the energy and electromechanical principles of mutual loading of traction electric machines is performed using the basics of generalization and systematization of physical quantities and concepts, the theory of electric circuits, the theory of mechanical systems, and the theory of electric machines. The analysis of thermal processes and energy parameters of the electric machine test system was performed using the theory of heating a homogeneous solid body and known methods of calculating thermal circuits. The results of theoretical studies have been confirmed experimentally. Findings. The analysis of the expression for determining the energy efficiency coefficient of heating the windings of traction electric machines, obtained in the work, shows that the starting current is the most rational when testing the traction motors of electric rolling stock of mainline transport for heating. The use of this load current allows reducing the electricity consumption for tests by 20-30% (compared to the hourly mode) without reducing the quality of tests, as well as reduces the time of heating tests by three to four times. Originality. The expediency of conducting the heating tests of traction motors of main electric rolling stock with a load current equal to the current of the start-up mode has been scientifically substantiated, which ensures the energy efficiency increase of the tests and a corresponding reduction in the total cost of electricity for acceptance tests. The method of analytical determination of the weighting coefficients of influence on the temperature excess of the armature winding of electric losses was proposed, the use of which allows evaluating the influence of the mutual loading modes of the tested traction electric machines on the discrepancy degree of the thermal loads of their armature windings. Practical value. The results of theoretical studies allow determining the rational modes of mutual loading of traction electric machines, which make it possible to reduce the electricity consumption for conducting their heating tests and shorten the time of conducting heating tests. In addition, it becomes possible to propose a method of evaluating the quality of acceptance tests of traction electric machines, which takes into account the discrepancy degree in the thermal loads of the windings.